2010
DOI: 10.1007/s00404-010-1696-6
|View full text |Cite
|
Sign up to set email alerts
|

Is the yolk sac a new marker for chromosomal abnormalities in early pregnancy?

Abstract: Currently available publications demonstrate a correlation between abnormal yolk sac size and miscarriage. However, in both cases a trisomy was confirmed. It should therefore be discussed whether form and size of the yolk sac could be a marker for chromosomal abnormalities of the fetus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…In the treatment of infertility patients, there is a desire to provide early reassurance. Ultrasound markers have been examined previously; the relationships of normal fetal cardiac activity (9)(10)(11)(12)(13)(14), the presence and size of a yolk sac (15)(16)(17)(18)(19)(20)(21), and the size of gestational sac to pregnancy outcomes have been reported (22)(23)(24)(25)(26)(27)(28). However, these studies had inherent limitations and have reported conflicting results.…”
mentioning
confidence: 94%
“…In the treatment of infertility patients, there is a desire to provide early reassurance. Ultrasound markers have been examined previously; the relationships of normal fetal cardiac activity (9)(10)(11)(12)(13)(14), the presence and size of a yolk sac (15)(16)(17)(18)(19)(20)(21), and the size of gestational sac to pregnancy outcomes have been reported (22)(23)(24)(25)(26)(27)(28). However, these studies had inherent limitations and have reported conflicting results.…”
mentioning
confidence: 94%
“…On the other hand, studies focusing on the shape or internal structure of the yolk sac have yielded conflicting results. Some studies suggest that irregular yolk sac shape and echogenic yolk sac can be associated with fetal death or abnormalities [5,[8][9][10]. In contrast, some authors claimed that a pregnancy could have a completely Fig 2. a-d.…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been proposed that SHYS changes may act as markers for some chromosomal abnormalities (Schmidt et al, 2011), it seems that the predictive value of SHYS measurements in determining the outcome of an early pregnancy is limited, as the alterations in SHYS size are the consequence of poor embryonic development or embryonic death rather than being the primary cause of early pregnancy failure (Jauniaux et al, 2005). This clinical perception agrees with morphological studies of the SHYS in spontaneous pregnancy loss, which revealed only non-specific, degenerative features related to embryonal death and retention (Nogales et al, 1992;Nogales et al, 1993;Nogales et al, 1995).…”
Section: Discussionmentioning
confidence: 99%